PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL PADA PERUSAHAAN TRANSPORTASI DI BURSA EFEK INDONESIA - Gamaliel, Joshua; Sudjarni, Luh Komang (E-Jurnal Manajemen, 2015)
The purpose of this study was to determine the effect of profitability , firm size and the asset structure of the capital structures on the transport companies in Indonesia stock exchange, in the year 2008-2012 . The research data obtained from the company's annual financial statements and hypothesis testing was done by using multiple linear regression analysis. The population in this study were all transportation companies listed on the Indonesia Stock Exchange 2008-2012 period with a total population of 28 transportation companies. The results of the study to obtain the proxy profitability (ROA) have significant negative effect on the capital structure, the size of the company and asset structure significant positive effect on the capital structure. Simultaneously profitability proxied ROA, firm size and asset structure significantly influence capital structure.
Keywords: profitability; firm size; asset structure; capital structure